Benefits of the fasting of Ramadan - Shehu, Fatmir Mehdi (2018)
Benefits of Fasting are to: (1) achieve Taqwa - Allah’s Conscience, (2) acquire the rewards of Allah and the ideal happiness and joy as well as the highest virtues and ideals; (3)give more Sadaqah and understand the principle of sincere love, self-purification; (4) understand the real spirit of social belonging, unity and brotherhood, of equality before Allah as well as before the law.